An effective stateless QoS routing for multimedia applications in MANET. (1st January 2014) - Raji, V.; Mohan Kumar, N.
In Mobile Ad-Hoc Networks (MANET), the increasing demand for multimedia application is more challenging and the existing routing protocols are not adequate owing to the complex design requirements of Quality of Service (QoS) routing. This paper proposes a stateless position-based solution for QoS routing issues and offers an efficient end-to-end communication guarantee. The proposed Stateless QoS (SQoS) routing protocol is based on adaptive compass greedy routing to determine a qualified path which satisfies the QoS requirements and the void handling scheme overcomes the local maximum issue. In addition, the SQoS routing utilises the node overhearing capacity to obtain the link quality measurement to provide a guarantee for efficient end-to-end transmission through the identification of high-quality links for multimedia streams. The performance of the proposed SQoS routing protocol is compared with existing QoS-GPSR. Finally, the performance evaluation proves that the SQoS routing protocols outperform the existing protocols.